Enhancing Defect Management in Strata Common Property: Stakeholder Perceptions and Process Improvement Strategies during the Liability Period — A Systematic Literature Review (Architecture Image Studies, 2025)
This study investigates the perceptions and lived experiences of strata managers, building owners, and contractors regarding current defect management processes for common property during the liability period. Drawing on a mixed synthesis of 16 qualitative and mixed-method studies from Malaysia, Australia, and other jurisdictions, the research explores operational, governance, and communication challenges that hinder effective defect rectification. The analysis identifies four recurring thematic issues: (1) information flow and communication gaps, (2) process inefficiencies and delays, (3) role ambiguity and accountability gaps and (4) financial and resource constraints. Stakeholders consistently call for standardized reporting systems, digital defect registers, and clearer governance frameworks to improve outcomes. The study proposes an integrated defect management framework emphasizing the use of digital platforms, enhanced stakeholder engagement, and proactive planning to reduce liability-period disputes and support asset sustainability. This research offers the first cross-regional synthesis linking stakeholder perceptions with practical, policy-oriented defect management reforms for strata properties, aligning with sustainable building operations and the industrial management focus of the built environment.